THE CHALLENGES FACED BY NIGERIAN WOMEN IN AGRICULTURAL ACTIVITIES: STUDY OF FORON WOMEN, 2010- 2023 - GUMAR MANJI KEFAS; MUTTANG S. FWANGMUN; UCHECHUKWU F. MUTBAM (International Studies Journal)
This paper is an attempt to appreciate the contribution of women in agricultural activities in Foron, thereby unleashing the full potential of women in agriculture which is not only a matter of gender equality but also a critical step towards achieving sustainable development goals, by recognizing and amplifying their roles in the agricultural sector. The paper also discusses challenges faced by women in agriculture and suggests ways through which these can be resolved in order to foster food security and self reliance. The appraisal of these challenges constitutes the main thrust.